Differences in scapular and humeral head position between swimmers and non-swimmers - McKenna, L.; Straker, L.; Smith, A.; Cunningham, J. (Scandinavian Journal of Medicine & Science in Sports, 2011)
The aims of this study were to determine differences between swimmers/non-swimmers, males/females and dominant/non-dominant sides for scapular and humeral head position, while accounting for size, and to determine the relationship between scapular and humeral head position. 46 teenage swimmers (30 females) and 43 non-swimmers (28 females) were measured. The distances between (a) medial spine of the scapula and T3/4 (Superior Kibler), (b) inferior scapula and T7/8 (Inferior Kibler) and (c) anterior acromion and anterior humeral head were recorded while teenagers stood with their hands-on hips. There was no main effect difference between swimmers and non-swimmers for scapular or humeral head position. There were interactions for swim status/dominance (Superior Kibler; P=0.005, Inferior Kibler; P<0.001) and swim status/gender (Superior Kibler; P=0.027). The humeral head was significantly further from the acromion on the dominant side (adjusted mean difference=1.4 mm, P=0.004). Little relationship between scapular and humeral head position was evident. Clinicians should be aware that swim status, in combination with gender or dominance may affect scapular position but does not affect humeral head position. Where swimming had an effect, it minimized differences between genders and sides. The small dominance effect on the humeral head position is unlikely to be clinically detectable.